RUNX1 inhibits the antiviral immune response against influenza A virus through attenuating type I interferon signaling - Yixiang Hu; Qi Pan; Kun Zhou; Yuehuan Ling; Hao Wang; Yan Li (Virology Journal, 2022)
Abstract Background Influenza A viruses (IAVs) are zoonotic, segmented negative-stranded RNA viruses. The rapid mutation of IAVs results in host immune response escape and antiviral drug and vaccine resistance. RUNX1 is a transcription factor that not only plays essential roles in hematopoiesis, but also functions as a regulator in inflammation. However, its role in the innate immunity to IAV infection has not been well studied. Methods To investigate the effects of RUNX1 on IAV infection and explore the mechanisms that RUNX1 uses during IAV infection. We infected the human alveolar epithelial cell line (A549) with influenza virus A/Puerto Rico/8/34 (H1N1) (PR8) and examined RUNX1 expression by Western blot and qRT-PCR. We also knocked down or overexpressed RUNX1 in A549 cells, then evaluated viral replication by Western blot, qRT-PCR, and viral titration. Results We found RUNX1 expression is induced by IAV H1N1 PR8 infection, but not by poly(I:C) treatment, in the human alveolar epithelial cell line A549. Knockdown of RUNX1 significantly inhibited IAV infection. Conversely, overexpression of RUNX1 efficiently promoted production of progeny viruses. Additionally, RUNX1 knockdown increased IFN-β and ISGs production while RUNX1 overexpression compromised IFN-β and ISGs production upon PR8 infection in A549 cells. We further showed that RUNX1 may attenuate the interferon signaling transduction by hampering the expression of IRF3 and STAT1 during IAV infection. Conclusions Taken together, we found RUNX1 attenuates type I interferon signaling to facilitate IAV infection in A549 cells.